2020
DOI: 10.3390/genes11040384
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of GABAergic Markers in the Forebrain of Young and Adult Engrailed-2 Knockout Mice

Abstract: Impaired function of GABAergic interneurons, and the subsequent alteration of excitation/inhibition balance, is thought to contribute to autism spectrum disorders (ASD). Altered numbers of GABAergic interneurons and reduced expression of GABA receptors has been detected in the brain of ASD subjects and mouse models of ASD. We previously showed a reduced expression of GABAergic interneuron markers parvalbumin (PV) and somatostatin (SST) in the forebrain of adult mice lacking the Engrailed2 gene (En2-/- mice). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Protein EN2 is mainly present in postnatal GABAergic neurons of the mouse hippocampus and cerebral cortex, and it was found that persistant high expression of EN2 during the prenatal and early postnatal period contributes to autism by affecting the maturation of Purkinje cell (PCs) in the cerebellum (James et al, 2013(James et al, , 2014. EN2 expression levels alter the number of GABAergic interneurons (Sgadò et al, 2013;Provenzano et al, 2020). Evidence from an in vitro study found that En2 increases the complexity of the dendritic tree of GABAergic neurons and reduced the number of mature synapses as well as the area of postsynaptic densities (Soltani et al, 2017).…”
Section: En2mentioning
confidence: 99%
“…Protein EN2 is mainly present in postnatal GABAergic neurons of the mouse hippocampus and cerebral cortex, and it was found that persistant high expression of EN2 during the prenatal and early postnatal period contributes to autism by affecting the maturation of Purkinje cell (PCs) in the cerebellum (James et al, 2013(James et al, , 2014. EN2 expression levels alter the number of GABAergic interneurons (Sgadò et al, 2013;Provenzano et al, 2020). Evidence from an in vitro study found that En2 increases the complexity of the dendritic tree of GABAergic neurons and reduced the number of mature synapses as well as the area of postsynaptic densities (Soltani et al, 2017).…”
Section: En2mentioning
confidence: 99%
“…Indeed, rare mutations, including de novo and intrinsic variants, have been found in the chromosome 15q11–q13 region, a site containing coding regions of specific subunits of GABA receptors, including GABRB3, GABRA5, and GABRG3 [ 289 , 290 , 291 , 292 ]. Finally, direct evidence of GABAergic dysfunction has been obtained from molecular and cellular studies in several genetic and pharmacological animal models of ASD [ 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 ]. Overall, the dysfunctions shown in both glutamatergic and GABAergic neurotransmission suggest a pathological switch in the E/I balance underlying, at least partly, the failure of compensatory mechanisms, such as adaptation of synaptic efficacy, plasticity, membrane excitability, and/or synapse numbers, physiologically implemented to prevent over-excitation [ 307 ].…”
Section: Gaba/glutamate Balance In Asdmentioning
confidence: 99%
“…TRN (Provenzano et al, 2020) Reduction of Pvalb mRNA (P30) Reduction in the number of PV + cells (6 weeks) VISUAL CORTEX (L2/3 and L5/6) (Pirone et al, 2020) Increase in the number of PV + cells (P30 and adult)…”
Section: Animal Ndd Models Of Asd With Reduced Pv Expression And/or Dmentioning
confidence: 99%